The role of physical activity in the resting state alpha oscillations of maturing brain : an MEG study - Karjalainen, Suvi (2017)
Although extensive research has focused on understanding the generation and modification of resting cortical activity, the underlying physiological and neural mechanisms still remain unknown. Thus, the purpose of this study was to investigate how physical activity and maturation are associated with resting cortical activity, and more accurately the maximum alpha power and the peak frequency of resting state. Resting cortical activity was measured from 63 adolescents between the age of 12 and 16 years using magnetoencephalography (MEG) while the participants were sitting relaxed eyes open for 3 minutes and eyes closed for 3 minutes. In addition, the total gray and white matter volumes were measured using magnetic resonance imaging (MRI). The participants were classified into low/moderate-activity (n=39) and higher-activity (n=22) groups based on their daily amount of moderate to vigorous physical activity. The MEG data was converted from its original domain to a representation in the frequency domain and individual averages for each brain area (left and right, parietal and occipital) and condition (eyes open and closed) were calculated from the resting state spectrum. A repeated measures analysis of variance (ANOVA) was performed to compare the maximum power and the peak frequency of the resting state between conditions and brain areas in different physical activity groups. Furthermore, the test of multiple mediation was applied to investigate the effects of physical activity and maturational measures on resting state. Among all participants, the maximum alpha power and the peak frequency were higher in eyes closed than in eyes open condition. The results revealed differences approaching significance in the maximum alpha power and the peak frequency between low/moderate-activity and higher-activity adolescents. Overall, low/moderate-activity group showed stronger alpha power and higher peak frequencies than higher-activity group. When the effects of physical activity and maturation on resting state were investigated, the results revealed that higher volume of gray matter was linked with higher alpha power in left parietal area. In addition, higher volumes of both gray and white matter were linked with higher alpha power in right parietal area. Furthermore, the association between puberty and alpha power in left occipital area was found to be mediated via gray and white matter volume. The differences in resting alpha power between the physical activity groups may be linked with differences in vigilance and arousal during non-task resting state. Differences in the peak frequencies between activity groups may indicate differences in white matter maturation or overall differences in the cognitive abilities. Although the relationship between physical activity, maturation and resting cortical activity seems highly complex, our findings imply that physical activity and pubertal maturation together may result in the modulation of resting cortical activity via structural maturation of the brain. However, further research is needed to investigate the underlying mechanisms modulating the resting cortical activity.